Chapter Hesperia, a Database for Palaeohispanic Languages; and AELAW, a Database for the Ancient European Languages and Writings. Challenges, Solutions, Prospects - Estarán, María José (De Gruyter, 2019)
This miscellaneous volume collects contributions on nineteen projects dealing with Digital Epigraphy - they are diversified in geographic and chronological context, for script and language, and for typology of digital output. The objective is to point out the methodological issues which are specific to the application of information technologies to epigraphy, with a focus on data modelling and text annotation, lexicography and interoperability.